High serum vitamin B12 binding capacity as a marker of the fibrolamellar variant of hepatocellular carcinoma. Issue 6345 (25th September 1982) - Paradinas, F J; Melia, W M; Wilkinson, M L; Portmann, B; Johnson, P J; Murray-Lyon, I M; Williams, R
Abstract : Ten (9.3%) of 107 patients with hepatocellular carcinoma had considerably increased serum unsaturated vitamin B12 binding capacity. All 10 were young (mean 12 years), had no serum alpha-fetoprotein, and no underlying cirrhosis; all had a longer survival compared with patients without increased serum unsaturated vitamin B12 binding capacity in the study. Seven of the 10 patients had fibrolamellar hepatocellular carcinoma, a recently recognised histological variant, which was found in only one young patient without increased serum unsaturated vitamin B12 binding capacity and no alpha-fetoprotein among the remaining 97. This high degree of correlation between increased serum unsaturated vitamin B12 binding capacity and fibrolamellar hepatocellular carcinoma has not been reported before. Increased serum unsaturated vitamin B12 binding capacity may be of considerable help in diagnosis, prognosis, and monitoring treatment of this well-defined group of patients with hepatocellular carcinoma but no alpha-fetoprotein.